Sparkle - Wilson, Lakita (Viking, 2023)
"Sparkle Moore is destined to be a star. Her mother is determined to turn her and her younger sister, Nova, into social media influencers and budding superstars. And after her dad has lost work as a sitcom actor, Sparkle wants to do whatever she can to help her family financially, too. But at the onset of middle school, Sparkle begins losing her hair--first her lashes, then her eyebrows, and then small circular bald spots appear in various sections on her head. It's hard enough having to go to school and hide her diagnosis from her friends--all while they're trying out for big roles in the school play--but Sparkle quickly has to deal with weird medications, itchy wigs, and lost opportunities her mom has wrangled, including a big shampoo commercial. Despite everything she might do to hide what's happening, and all her work keeping her friends together, when Sparkle's secrets start coming to the surface--Sparkle has to come to terms with the changes in her life and show her classmates and her family what she can do with or without hair" --